2016
DOI: 10.1002/bjs.10179
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with increased prevalence of abdominal aortic aneurysm in women

Abstract: This report should stimulate consideration of a targeted AAA screening programme for women aged over 65 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Interestingly, the authors built up a model that included other variables such as history of stroke, hypertension, smoking, ankle brachial index, atrial fibrillation, and carotid stenosis, and identified a subgroup of female participants with an AAA prevalence of 1.57%. 48 This figure is similar to that found in the metaanalysis here (1.4%), suggesting that female patients undergoing TTE for cardiac disease may have demographic characteristics and comorbidities similar to those included in the high risk model proposed by Chabok et al 48 The findings in the present study could therefore provide an evidence basis to recommend opportunistic screening for AAA in female patients during TTE.…”
Section: Newcastleeottawa Scale Itemsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, the authors built up a model that included other variables such as history of stroke, hypertension, smoking, ankle brachial index, atrial fibrillation, and carotid stenosis, and identified a subgroup of female participants with an AAA prevalence of 1.57%. 48 This figure is similar to that found in the metaanalysis here (1.4%), suggesting that female patients undergoing TTE for cardiac disease may have demographic characteristics and comorbidities similar to those included in the high risk model proposed by Chabok et al 48 The findings in the present study could therefore provide an evidence basis to recommend opportunistic screening for AAA in female patients during TTE.…”
Section: Newcastleeottawa Scale Itemsupporting
confidence: 88%
“…Similarly, Ulug et al 47 in a recent metaanalysis recorded a pooled AAA prevalence of 0.74% among female participants. A contemporary study by Chabok et al, 48 which investigated the AAA prevalence in women in the UK, found an overall prevalence of 0.29% for individuals aged 66e85 years. Interestingly, the authors built up a model that included other variables such as history of stroke, hypertension, smoking, ankle brachial index, atrial fibrillation, and carotid stenosis, and identified a subgroup of female participants with an AAA prevalence of 1.57%.…”
Section: Newcastleeottawa Scale Itemmentioning
confidence: 99%
“…13e15 AAA and atherosclerosis may share some risk factors, such as age, smoking, hypertension, and hyperlipidaemia. 16 A metaanalysis demonstrated that the prevalence of AAA is approximately 2.4 times higher among patients with a history of coronary artery disease (CAD) compared with the general population without CAD. 17 It was assumed that screening for AAA in these higher risk populations may be more effective.…”
Section: Introductionmentioning
confidence: 99%
“…Among the risk factors for the development of AAA are age, gender, hypertension, positive family history and coronary artery disease [5]. Diabetes seems to have a protective effect on the formation of AAA [6,7]. One of the causes of Marcin Piotr Żelezik et al, AAA screening program in Swietokrzyskie Voivodeship: early results high mortality is the asymptomatic occurrence of AAA.…”
Section: Introductionmentioning
confidence: 99%